The Influence of Waqf Literacy, Trust, and Religiosity on Interest in Cash Waqf: (Islamic Finance and Banking Study Program, Medan State Polytechnic, Medan City, North Sumatra Province, Indonesia) - Nazwa Raissa Zahira; Widia Dahmira; Nova Zahara Tianra Rikana; Rizal Agus (Ecopreneur : Jurnal Ekonomi dan Bisnis Islam, 2026)
This study aims to examine the influence of waqf literacy, trust, and religiosity on the intention to perform cash waqf in Indonesia, considering that its realization remains below its potential. The research employed a quanti-tative approach with an explanatory research design using a survey method through a five-point Likert scale questionnaire distributed to 35 respondents selected purposively based on the criteria of being Muslim, at least 17 years old, and having knowledge of cash waqf. Data were analyzed using multiple linear regression with SPSS 25 after conducting validity, reliability, and classical assumption tests. The results indicate that partially, waqf literacy and trust do not significantly affect cash waqf intention, whereas religiosity has a positive and sig-nificant effect and is the most dominant variable. Simultaneously, the three variables significantly influence cash waqf intention with an Adjusted R² of 0.532, meaning that 53.2% of the variance in intention is explained by the model, suggesting that strengthening religiosity, enhancing waqf education, and improving institutional transparency are crucial strategies to increase cash waqf participation. Keywords: Waqf Literacy, Trust, Religiosity, Cash Waqf Intention